Development of an Android-based Barbershop Information System for Queue Management and Financial Reporting - Nanang Kurniawan; Novi Setiani (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2026)
The rapid advancement of information technology has encouraged various sectors, including the barbershop industry, to adopt digitalization in order to improve service quality and operational efficiency. However, customer queue management and financial reporting in many barbershops are still handled conventionally, making the processes less effective and more prone to errors. This study aims to design an Android-based mobile application prototype called Barber-Link to support digital queue management and financial reporting. The development method employed in this research was the Prototype method, while system modeling utilized Unified Modeling Language (UML) as a supporting tool. The result of this study is an Android-based prototype system equipped with key features such as customer queue management, transaction data recording, and a financial reporting dashboard. These features are designed to assist barbershop owners in managing customer queues while simplifying financial reporting processes, making operations more effective and efficient.